In Silico Analysis of Gene Expression Location and Single Nucleotide Polymorphisms (SNPs) of The Glucagon Like Peptide 1 Receptor (GLP-1R) - Rita Maliza; Putra Santoso; Bramadi Arya; Alimuddin Tofrizal; Rarastoeti Pratiwi (Bogor Agricultural University, Indonesia, 2023)
Association studies of SNPs have become very important in determining how genetic variants are linked to complex diseases, quantitative traits, and physiological responses. Genetic polymorphisms in the GLP-1R gene have potentially decreased protein stability and are associated with many diseases, especially diabetes and obesity. This study aimed to screen the expression and investigate the genetic polymorphism of the GLP-1R by using several beneficial bioinformatics tools. We observed database Ensembl, GTEx portal, and KEGG to identify the structure, expression, and molecular pathway of GLP-1R. In silico computational methods (SIFT, PolyPhen v2, PROVEAN, and PhD-SNP) were used to identify nsSNPs of the GLP-1R that potentially influence protein structure and function. I-Mutant was used to investigate possibly damaging nsSNPs, while GeneMANIA was used to investigate GLP-1R gene-gene interactions. GLP-1R is localized on chromosome 6p21, contains 13 exons, and has the regulation variant (CTCF, promotor, enhancer, and promotor flank region). GLP-1R is highly expressed in the pancreas to stimulate glucose-dependent insulin secretion and suppress glucagon secretion. Seven nsSNPs of the GLP-1R gene were found to be potentially deleterious: rs10305421, rs201672448, rs10305492, rs2295006, rs6923761, rs1042044, rs140642887, and rs10305510. I-Mutant server showed that nsSNPs rs140642887 was unstable, decreased GLP-1R protein stability, and impaired other genes' interaction and function (SP1, SP3, GNAS, and GCG). This study is the first in silico analysis of the polymorphic GLP-1R gene, and will serve as a great resource for developing precision medications to treat diseases associated with these polymorphisms.